Immediate breast reconstruction after mastectomy--why do women choose this option? - Shameem, H.; Yip, C.H.; Fong, E. (West Asia Organization for Cancer Prevention, 2008)
Only a third of patients undergoing mastectomy were offered immediate reconstruction. In public hospitals in developing countries, limited operating time and availability of plastic surgery services are major barriers to more women being offered the option.